Folding Mitochondrial-Mediated Cytosolic Proteostasis Into the Mitochondrial Unfolded Protein Response - Jenkins, Edmund Charles; Chattopadhyay, Mrittika; Germain, Doris (Frontiers in Cell and Developmental Biology, 2021)
Several studies reported that mitochondrial stress induces cytosolic proteostasis. How mitochondrial stress activates proteostasis in the cytosol remains unclear. However, the cross-talk between the mitochondria and cytosolic proteostasis has far reaching implications for treatment of proteopathies including neurodegenerative diseases. This possibility appears within reach since selected drugs have begun to emerge as being able to stimulate mitochondria-mediated cytosolic proteostasis. In this review, we focus on studies describing how mitochondrial stress activates proteostasis in the cytosol across multiple model organisms. We propose a model linking mitochondria-mediated regulation of cytosolic translation, folding capacity, ubiquitination and proteasome degradation as a multi layered control of cytosolic proteostasis that overlaps with the integrated stress response (ISR) and the mitochondrial unfolded protein response (UPRmt). By analogy to the conductor in an orchestra managing multiple instrumental sections into an dynamically integrated musical piece, the cross-talk between these signaling cascades places the mitochondria as a major conductor of cellular integrity.